Well-being and spiritual intelligence predict attitudes of adolescents’ towards violence - EKŞİ, HALİL (My University, 2022)
In this study, it is aimed to examine the relationships between the well-being, spiritual intelligence and attitudes of adolescents living in Turkey towards violence. The sample of the study consists of 466 high school students (194 girls, 272 boys) aged between 14 and 19, selected using the convenience sampling method. In the study, “Scale for Spiritual Intelligence”, “Five-Dimensional Well-being for Adolescents (EPOCH) Scale” and “Attitude towards Violence Scale for Adolescents” and demographic information form were used as measurement tools. Hierarchical regression analysis was used to test the predictiveness of adolescents’ well-being and spiritual intelligence on their attitudes towards violence. According to the findings obtained from the research, there is a moderately negative and significant relationship between attitude towards violence and well-being. It is seen that there is a low negative and significant relationship between attitude towards violence and spiritual intelligence. It was identified that there is a moderate positive and significant relationship between well-being and spiritual intelligence scores. The wellbeing variable explaining 32% of the attitude scores towards violence was first included in the staged multiple regression analysis performed. And in the second stage, the spiritual intelligence variable, which contributes 2% to the explained variance, was also included. When the total variance explained is examined, it is seen that the variables of well-being and spiritual intelligence together explain 34% of the total variance in the attitude scores towards violence. This finding shows us that the change in well-being and spiritual intelligence scores predicts the change in the scores of the attitude towards violence

Bu çalışmada Türkiye’de yaşayan ergenlerin iyi oluş, manevi zekâ ve şiddete yönelik tutumları arasındaki ilişkilerin incelenmesi amaçlanmıştır. Araştırmanın örneklemini elverişlilik örnekleme yöntemi kullanılarak seçilen, yaşları 14 ile 19 arasında değişen 466 lise (194 kız, 272 erkek) öğrencisi oluşturmaktadır. Araştırmada ölçme aracı olarak “Manevi Zekâ Ölçeği (SIS)”, “Ergenler İçin Beş Boyutlu İyi Oluş (EPOCH) Ölçeği” ve “Ergenler için Şiddete Yönelik Tutum Ölçeği” ve Demografik Bilgi Formu kullanılmıştır. Ergenlerin iyi oluşlarının ve manevi zekalarının şiddete karşı tutumları üzerindeki yordayıcılığını test etmek için hiyerarşik regresyon analizi kullanılmıştır. Araştırmadan elde edilen bulgulara göre; şiddete yönelik tutum ile iyi oluş arasında orta düzeyde negatif ve anlamlı bir ilişki bulunmaktadır. Şiddete yönelik tutum ile manevi zekâ arasında düşük düzeyde negatif ve anlamlı bir ilişki olduğu görülmektedir. İyi oluş ile ve manevi zekâ puanları arasında orta düzeyde pozitif ve anlamlı bir ilişki olduğu belirlenmiştir. Yapılan aşamalı çoklu regresyon analizine ilk olarak şiddete yönelik tutum puanlarının %32’sini açıklayan iyi oluş değişkeni alınmıştır. İkinci aşamada ise açıklanan varyansa %2 katkı sağlayan manevi zekâ değişkeni de dahil edilmiştir. Açıklanan toplam varyansa bakıldığında ise, iyi oluş ve manevi zekâ değişkenlerinin birlikte şiddete yönelik tutum puanlarındaki toplam varyansın %34’ünü açıkladığı görülmektedir. Bu bulgu bize iyi oluş ve manevi zekâ puanlarındaki değişimin şiddete yönelik tutum puanlarındaki değişimi yordadığını göstermektedir.
Keywords: Turkish adolescents; Spiritual intelligence; Adolescence; Well-being; Violence; Türk ergenler; Manevi zeka; Ergenlik; İyi oluş; Şiddet